A way with words : vocabulary development activities for learners of english, book 3 - Redman, Stuart (Cambridge : Cambridge University Press, 1991)
This text takes a learner-centred and creative approach to vocabulary learning. It combines a teacher's book, a student's book and a cassette. The cassette contains the recordings for the listening exercises and pronunciation checks of difficult words and phrases at level 3.
Keywords: English language -- Semantics -- Study and teaching; Vocabulary -- Study and teaching